Diruthenium complexes having a partially hydrogenated bipyridine ligand: plausible mechanism for the dehydrogenative coupling of pyridines at a diruthenium site. (12th September 2019) - Takao, Toshiro; Kawashima, Takashi; Nagae, Ryo; Kanda, Hideyuki; Watanabe, Wataru
Abstract : Diruthenium complexes containing a partially hydrogenated bipyridine ligand are synthesized, which undergo dehydrogenation leading to the elimination of bipyridine. Abstract : The reactions of the diruthenium tetrahydrido complex, Cp*Ru(μ-H)4 RuCp* (1 ) (Cp* = η 5 -C5 Me5 ), with pyridines were investigated in relation to the dehydrogenative coupling of 4-substituted pyridines. Complex 1 reacted with γ-picoline to yield the bis(μ-pyridyl) complex, {Cp*Ru(μ-H)(μ-4-MeC5 H3 )}2 (2a ), with the elimination of dihydrogen. Complex 2a immediately reacted with the liberated dihydrogen to yield μ-η 2 -dihydrobipyridine (dhbpy) complex 4a via C–C bond formation between the two pyridyl groups, in which one of the pyridine rings underwent partial hydrogenation. The X-ray structure of 4a shows that the dhbpy moiety adopts a μ-η 2 coordination mode at the Ru2 site. Complex 4a was reversibly converted to 5a via the elimination of dihydrogen in which the dhbpy moiety adopts a μ-η 2 :η 2 mode. Although 5a was coordinatively saturated, 5a readily reacted with t BuNC to yield 6a . This was owing to the ability of the dhbpy ligand changing its coordination mode between the μ-η 2 :η 2 and μ-η 2 modes. This also causes the dehydrogenation from the dhbpy ligand to yield μ-η 2 :η 2 -bipyridine complex 7a at 140 °C. However, 7a was not shown to be an intermediate of the catalysis. The reaction of 1 with 1, 10-phenanthroline afforded μ-η 2 -phenanthroline complex 8 containing two hydrides, which can be a model compound for the bipyridine elimination from the Ru2 site. Dynamic NMR studies suggested that 8 was isomerised to an unsaturated μ-N-heterocyclic carbene (NHC) complex. The unsaturated nature of the μ-NHC complex is likely responsible for the uptake of the third pyridine molecule to turn over the catalytic cycle.